1979
DOI: 10.1002/iroh.19790640103
|View full text |Cite
|
Sign up to set email alerts
|

The Size‐Depth Relationship in Deep Ocean Animals

Abstract: In response to THIIL'S (1975) hypothesis that the food-limited deep sea is a small organism habitat, further data on average size of individnals representing various deep-sea taxa are presented. Our data were gathered with trawls and box corers between 200 and 5000 meters, in the western Noi.th Atlantic. For echinoderms, decapods and macrofauna there appears to be no steady, logarithmic decline i n size with increasing depth, bnt fishes are biggerdeeper. : . uith developmental notes on cert.ain myct.0phids. -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
2
2

Year Published

1980
1980
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 12 publications
8
48
2
2
Order By: Relevance
“…Polloni et al (1979) and Snelgrove and Haedrich (1985) reported the "bigger-deeper" phenomenon, on the South of Newfoundland's continental slope, for Antimora rostrata, Synaphhobranchus kaupi and Nezumia bairdi.…”
Section: Resultsmentioning
confidence: 99%
“…Polloni et al (1979) and Snelgrove and Haedrich (1985) reported the "bigger-deeper" phenomenon, on the South of Newfoundland's continental slope, for Antimora rostrata, Synaphhobranchus kaupi and Nezumia bairdi.…”
Section: Resultsmentioning
confidence: 99%
“…Within the deep marine environment, patterns of changing animal size with depth have been demonstrated in invertebrates (Thiel 1975;Haedrich & Rowe 1977;Rex & Etter 1998;Olabarria & Thurston 2003) and fish (Polloni et al 1979;Macpherson & Duarte 1991). Early studies of the demersal deep-sea ichthyofauna indicated a general pattern of increased size with depth (Polloni et al 1979), which came to be known as Heincke's Law (following Heincke's (1913) description of the size of plaice in the North Sea).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of the demersal deep-sea ichthyofauna indicated a general pattern of increased size with depth (Polloni et al 1979), which came to be known as Heincke's Law (following Heincke's (1913) description of the size of plaice in the North Sea). However, subsequent work demonstrated that the phenomenon was not ubiquitous (Snelgrove & Haedrich 1985), may be an artefact of sampling (Merrett et al 1991b) and in some regions a decline in size with depth has been reported (Stefanescu et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Body mass is a fundamental attribute of any animal and has an additional interest because most biological processes are scaled to the size of the organism (Peters, 1983). The analysis of size distributions in deep-sea fish studies focuses mainly on size depth relationships both for individual species and for the whole fauna (Haedrich and Rowe, 1977;Polloni et al, 1979;Merrett and Marshall, 1981;Sulak, 1982;Pearcy et al, 1982;Carney et al, 1983;Mauchline and Gordon, 1984;Middleton and Musick, 1986;Gordon and Duncan, 1987;Macpherson and Duarte, 1991;Merrett et al, 1991;Stefanescu et al, 1992). The causes pointed out by these authors to explain changes of size with depth are related mainly to food availability, interor intra-specific competition and predation.…”
Section: Introductionmentioning
confidence: 99%